Leveraging the kinetic isotope effect by compact H-bond motifs for electrochemical hydrogen isotope separation - Guobin Wen; Haiqi Liang; Shuxuan Liu; Ningce Zhang; Shuai Chen; Guoqiang Shen; Tehua Wang; Ru Chen; Li Tao; Bohua Ren; Shuangyin Wang (Proceedings of the National Academy of Sciences, 2026)
Electrochemical hydrogen isotope separation has been constrained for decades by the similar energy barriers of the rate-determining O–H and O–D bond cleavage step in water isotopologues. Herein, we compact H-bond connectivity through screening a series of additives to stimulate electrochemical proton quantum tunneling (QT) behaviors of “through-barrier”, which are virtually impossible for heavier D-relevant motions. The average H-bond length of H 2 O⋯OH − is 3.4% shorter (2.78 Å) with isopropanol additive at the engineered interface. Fundamentally, QT effects are magnified by selectively promoting proton transfer-involved reactions through strengthening the H-bond and filling the H-bond gap, which are further proved by both experimental Arrhenius plots with near small-curvature tunneling approximation and a stronger proton excursion in path integral molecular dynamics simulations. Hence, a record-high H 2 O separation factor of 276 is realized at room temperature with a three-order-of-magnitude growth of H/D kinetic isotope effect constant up to 10,165. Significantly, a large-scale multistage reactor is engineered to obtain continuous enrichment of heavy water with a deuterium atomic fraction over 80%.